Treatments and therapeutic protocols for the recovery of an asphyxiated new-born: A review of pre-clinical and clinical studies in human neonates and in different animal models - Islas-Fabila, Paloma; Orozco-Gregorio, Hector; Roldan-Santiago, Patricia; Waytula, Marilyn; Gonzalez-Hernandez, Milagros; Vega-Manriquez, Xochil; Jimenez-Collado, Carlos Antonio; Bonilla-Jaime, Herlinda (Veterinarni medicina, 2022)
The objective of this review is to ascertain the advantages and disadvantages of several treatments and therapeutic protocols that have been used for the prevention and treatment of perinatal asphyxia in human neonates and in different animal models. Perinatal asphyxia is one of the main causes of mortality worldwide and is an important factor in triggering physio-metabolic disorders that result in serious neurological consequences and learning disorders not only in human foetuses and neonates, but also in animals. In recent years, the search for new pharmacological protocols to prevent and reverse physio-metabolic disorders and brain damage derived from perinatal asphyxia has been and continues to be the subject of intense research. Currently, within these pharmacological protocols, therapeutic strategies have been evaluated that use respiratory and hormonal stimulants, as well as hypothermic therapies in combination with other putative neuroprotective agents. Similarly, energy supplements have been evaluated with the objective of preventing perinatal asphyxia and treating new-borns with this condition, and to decrease the incidence of neonatal and foetal deaths associated with it. However, despite these promising advances, this pathology has persisted, since the administration of these therapies in low doses may not exert a neuroprotective effect or, in high doses, can trigger adverse effects (such as reduced cardiac contractility, reduced cerebral blood flow, poor perfusion, sympathetic and neuroendocrine stimulation, and increased blood viscosity) in human foetuses and neonates as well as in different animal models (rats, piglets, sheep and rabbits). Therefore, it is important to determine the minimum effective dose with which these therapies exert a neuroprotective effect, as well as the mode of administration, the duration of therapy, etc. Therefore, until a powerful strategy is found to improve the consequences of suffocation, this topic will continue to be the subject of intensive research in the future.
Keywords: hypoxic-ischemic encephalopathy; neonatal mortality; perinatal asphyxia